2018
DOI: 10.1186/s12901-018-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Generic quality of life in persons with hearing loss: a systematic literature review

Abstract: BackgroundTo the best of our knowledge, no empirically based consensus has been reached as to if, and to what extent, persons with hearing loss (HL) have reduced generic Quality of life (QoL). There seems to be limited knowledge regarding to what extent a hearing aid (HA) would improve QoL. The main aim of the present study was to review studies about the relationship between HL and QoL. A supporting aim was to study the association between distress and HL.MethodsLiterature databases (Cinahl, Pub Med and Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 64 publications
4
81
2
4
Order By: Relevance
“…The quality of life affects individuals' physical health, psychological experience and social relations [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of life affects individuals' physical health, psychological experience and social relations [25].…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of hearing loss and low accessibility of hearing aids, it is imperative to conduct high-quality studies to gure out the e cacy of wearing hearing aids. Systematic reviews on hearing and quality of life have found that a majority of previous studies were cross-sectional studies and only a few were conducted in developing countries [25,26]. Most studies agree that hearing aids use raises quality of life, such as improving social function in Short Form 36 Health Survey (SF-36) [27], reducing risk of anxiety and depression in EuroQoL 5-Dimension (EQ-5D) [28].…”
Section: The Intervention Of Hearing Aids Usementioning
confidence: 99%
“…Progression in hearing loss cannot be remediated; therefore, optimal management of this condition not only requires early recognition and rehabilitation, but it also should include an evaluation of QoL status and its assessment [19][20][21][22] . According to the study by patients reporting hearing loss shows weak correlation each other, so we need new scales to asses the subjects with hearing loss 24 . In our study, kinesiophobia was significantly correlated with physical health score and hearing frequencies in study group.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of hearing loss is often multifactorial and not isolated to reduced hearing and increased listening effort. For example, it can negatively impact on the ability to communicate, which amplifies social isolation, and can lead to relationship difficulties and reduced well-being [2, 3]. In addition, the presence of uncorrected hearing loss increases the risk of cognitive decline and dementia [4, 5].…”
Section: Introductionmentioning
confidence: 99%